Forecasting financial crises and contagion in Asia using dynamic factor analysis - Andrea Cipollini; George Kapetanios (Queen Mary University of London, Department of Economics, 2005)
In this paper we compare the performance of a regional indicator of vulnerability in predicting, out of sample, the crisis events affecting the South East Asian region during the 1997-98 period. A Dynamic Factor method was used to retrieve the vulnerability indicator and stochastic simulation is used to produce probability forecasts. The empirical findings suggest evidence of financial contagion.
Keywords: C32; C51; F34; 330; Financial contagion; Dynamic factor model; Dynamisches Modell; Prognoseverfahren; Sch\~AƒÂtzung; S\~AƒÂdostasien; Finanzmarktkrise